2018
DOI: 10.1002/app.46923
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of antibacterial waterborne fluorinated polyurethane

Abstract: Antibacterial waterborne polyurethanes (WPUs) have attracted increasing attention in a wide range of industrial applications because of their versatile properties as well as ecofriendly nature. Although extensive research has been carried out on antibacterial WBPU synthesis, the roles of some of the key synthesis components remain unclear. In this study, the novel chain extender DMG (dimethylol propionamide containing guanidine group) was designed and synthesized, which has not been reported before. DMG and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 36 publications
(36 reference statements)
0
18
0
Order By: Relevance
“…From Figure b, it could be found that although the particle size of WPU- g -PDMS x was different, the particle size distribution was nearly equal, suggesting that the WPU- g -PDMS x grafted with different amounts of hydrophobic PDMS chains might be distributed in water uniformly to produce a stable dispersion . Compared to the WPU dispersion with an average particle size of 33.0 nm, the particle size of WPU- g -PDMS x dispersions increased from 61.9 nm to 78.6, 94.2, 119.5, and 121.6 nm, as the PDMS content increased from 1.0 wt % to 2.0, 3.0, 4.0, and 5.0 wt %, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…From Figure b, it could be found that although the particle size of WPU- g -PDMS x was different, the particle size distribution was nearly equal, suggesting that the WPU- g -PDMS x grafted with different amounts of hydrophobic PDMS chains might be distributed in water uniformly to produce a stable dispersion . Compared to the WPU dispersion with an average particle size of 33.0 nm, the particle size of WPU- g -PDMS x dispersions increased from 61.9 nm to 78.6, 94.2, 119.5, and 121.6 nm, as the PDMS content increased from 1.0 wt % to 2.0, 3.0, 4.0, and 5.0 wt %, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…This may be due to the increased crosslinking density resulting from the introduction of Lys. Among them, the electron cloud-rich N elements from amino groups in Lys can form numerous hydrogen bonds, 31 which restrict the movement of molecular chains and then enlarge the particle size of WKPU. In addition, the large dispersion index (PDI) of WKPU emulsions can be interpreted as an increase in the degree of cross-linking that hinders the movement of molecular chains, thus affecting the uniform growth of molecular chains and the inhomogeneity of molecular lengths and branching.…”
Section: Resultsmentioning
confidence: 99%
“…PU nanocomposites, having superior mechanical properties and biocompatibility, are potentially candidate materials to be used as antibacterial coatings on implants and other medical devices [23,24]. In actual use, various PU materials that have been developed as coatings for implanted medical devices also contain bactericide or contact bactericide [25][26][27][28]. Typically, these antimicrobial compounds are different nanoparticles (silver, copper, ZnO, SiO2, or organoclays) that interfere with bacteria and/or other microorganisms on contact [25][26][27][28], but there is an increasing need to design new and effective PU nanocomposites for coating applications.…”
Section: Introductionmentioning
confidence: 99%